Analisis Kitab Kaifiyyah Mengadakan Wakaf Muslimin Karangan Syeikh Junid Tola (M.1948): Descriptive Analysis of Kitab Kaifiyyah Mengadakan Wakaf Muslimin Authored by Syeikh Junid Tola (d. 1948) - Mohd Paid, Muhammad Amirul Solehin; Abdul Niri, Mohammaddin; Ali, Abdul Karim; Abdul Rahman, Noor Naemah (Jurnal Fiqh, 2024)
The Kitab Kaifiyyah Mengadakan Wakaf Muslimin, authored by Sheikh Junid Tola (d. 1948), is a rare Jawi literature that explains the practical implementation of Islamic endowment (waqf) as applicable to the Malay community of that era. In the context of historiography of fiqh on waqf, this study examines whether the book reflects a paradigm that carries regressive or progressive values. The research framework was formed based on qualitative research with data collection using the library method, while data analysis was guided by the content analysis method. The findings reveal 88 textual data in this book that are relevant to the development of waqf which results from 6 main sources, namely paddy field, zakat, rupi currency, land, business and craftmanship. Based on these textual data, it can be concluded that the concept of waqf development in Kitab Kaifiyyah is not only aligned with the principles of waqf in classical Islamic literature but is also progressive in accommodating the local circumstances of the Muslim community at that time.